Isohumulones – a Review - Kappler, Sebastian; Schönberger, Christina; Krottenthaler, Martin; Becker, Thomas (BrewingScience, 2010)
Isohumulones, an isomerisation product from hop (humulus lupulus sp.) derived humulones are the main bittering substance in beer. They contribute to more than 85 % of the allover bitterness of beer [65]. Hops and its constituents as well as its application in the brewery is subject of investigations for more than a century already. Hops as an ingredient in beer has been used since the early Middle Ages. The objective back than was to save beer from microbiological spoilage and to use the hops as a flavouring ingredient [6]. Today we know that hops and its constituents also improve foam stability and contributes to the flavour stability of beer in various ways [71]. This paper gives a short overview about the most important literature which was published throughout the last decades.